ANALYSIS OF GROWTH PERFORMANCE AND FEED EFFICIENCY OF GIANT GOURAMY (Osphronemus gouramy) THROUGH THE ADDITION OF CHITOSAN AND PROBIOTICS - Khayrurraja, Ayja; Grandiosa, Roffi; Pratiwy, Fittrie Meyllianawaty; Iskandar, Iskandar (Jurusan Perikanan dan Kelautan, 2023)
The purpose of this study was to determine the optimum level of addition of chitosan and probiotics in feed to increase the growth rate and daily feed consumption of giant gouramy (Osphronemus gouramy). The method used in this research is an experimental method of completely randomized design (CRD), which consists of five treatments and three replications. The treatments used were (A) without giving chitosan and probiotics (control), (B) giving chitosan at 7.5 g/kg feed and probiotics at 10 ml/kg feed, (C) giving chitosan at 7.5 g /kg feed and probiotics at 15 ml/kg feed, (D) chitosan at 7.5 g/kg feed and probiotics at 20 ml/kg feed, (E) chitosan at 7.5 g/kg feed and probiotics of 25 ml/kg feed. The parameters measured were absolute length absolute weight, specific growth rate, feed utilization efficiency ratio (EPP), survival rate, and water quality. Data were analyzed using the Anova test at the 5% level. The results showed that the addition of different concentrations of chitosan and probiotics to commercial feeds could affect growth, and EPP but did not affect the survival rate of giant gouramy. The results obtained during the study showed that treatment C with the addition of chitosan of 7.5 g/kg of feed and probiotics of 15 ml/kg of feed resulted in the highest absolute length growth of 4.87 cm, the highest absolute weight growth of 19,35 g, the highest daily growth rate was 46,08%, the feed efficiency was 91,5% and survival rate was 97,78%. Whereas in terms of the effectiveness of treatment B with the addition of chitosan 7.5 g/kg of feed and less probiotics, namely as much as 10 ml/kg of feed, the treatment was as good as treatment C.